A study of maternal risk factors and the perinatal outcome in meconium stained amniotic fluid in central referral hospital - Niranjan, Kapil Singh; Lucksom, Pesona Grace (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Meconium staining of amniotic fluid (MSAF) is a significant risk factor for the subsequent development of meconium aspiration syndrome (MAS), respiratory distress and eventual respiratory failure in neonates. To learn more about the risk factors and outcomes associated with MSAF, a prospective case control study was conducted. The objective of the study was to study various maternal risk factors associated with MSAF and to study the outcome of neonates born through MASF and to compare the perinatal outcome in patients with thick and thin meconium stained amniotic fluid. Methods: A hospital based prospective case control study was conducted comparing pregnant women with meconium stained (cases) amniotic fluid with pregnant women having clear liquor (control), 200 in each arm. Singleton pregnancies complicated with MASF were included in the cases group on the basis of predefined inclusion criteria. Various risk factors, mode of delivery, outcome of neonates and perinatal outcome in babies born through thick and thin meconium stained amniotic fluid was studied. Results: Out of 200 patients who had MSAF 114 patients (57%) had thick meconium stained liquor while remaining 86 patients (43.00%) had thin meconium stained amniotic fluid. Post-maturity, pregnancy induced hypertension; oligohydramnios and prolonged labor were found to be statistically significant risk factors for MSAF. Nonreactive non-stress test and Need for cesarean section was more common in women with MSAF as compared to women with clear liquor (p <0.05). Common morbidities in neonates were Birth asphyxia (15%) followed by meconium aspiration syndrome (10%) and hypoxic ischemic encephalopathy (15%). Conclusions: Meconium stained amniotic fluid is more commonly associated with post-maturity, pregnancy induced hypertension, oligohydramnios and prolonged labor low APGAR score and higher incidence of birth asphyxia and NICU admissions. Appropriate management of neonates with meconium aspiration syndrome is crucial to prevent neonatal mortality.